Role of Personality Characteristics and Family Communication Patterns in Predicting Couple Burnout among Employee in Iranian Oil Terminals Co - Ahmadi, Zari (International Journal of Applied Behavioral Sciences, 2017)
Couple burnout is a painfully physical, emotional and psychological exhaustion, consequences such as marital dissatisfaction and ultimately leads to divorce. The present study aimed to investigate of the Studying Personality Characteristics and the Role of Family Communication Patterns in Predicting Couple Burnout in Employees of Iranian Oil Terminals Company. For this purpose, in a descriptive study, correlational type, 200 employees were selected among married employees of Iranian oil Terminals Company.They were selected in a form of simple sampling randomly. They were tested with personality questionnaire, )NEO , Costa & McCrae), Family communications patterns questionnaire (Christensen & Sullaway) and couples burnout (Pines).For data analysis correlation coefficient and multiple regression were used. The result indicated that the except openness factor, other personality Characteristics had significant relation with couple burnout and this relation for Neuroticism was positive significant and for extraversion, agreeableness and conscientiousness. Were negative significant relation. The result also indicated that relationship between all Component communication patterns and couple burnout had significant relation and this relationship for mutual constructive communication was negative significant and for other three subscales were positive significant. The result also indicated mutual constructive communication pattern and, man Expectance / woman avoidance, woman Expectance / man avoidance predicted couple burnout. Neuroticism was the only attribute of the personality Characteristics that able to predicted couple burnout.